Culture of Siri' in Learning Akidah Akhlak in MAN Suli Luwu District - Yunus Yunus; Nurseha Nurseha; Maemunah Maemunah (JIEBAR : Journal of Islamic Education: Basic and Applied Research, 2020)
The application of siri' culture in learning akidah akhlak is reflected in the attitudes of students through discipline and responsibility. Discipline and responsibility of students are dignity, and self-respect which is a reflection of the height of siri'. Enforce good discipline through the code of ethics of students. 2) The culture of siri' functions as the spirit of students in the educational process. The values of akidah and morals which are summarized in the values of Divinity (ilahiyah), Humanity, and Naturalness have in common with the values of siri' which are summarized in the elements of siri': Pajjama, Lempu', Getteng, and Sipakatau. 3) The internalization of siri' culture in learning akidah akhlak is a must because implementing the culture of siri' is the same as applying Islamic values.